Efektivitas Penggunaan LMS (Learning Management System) dalam Diklat Daring untuk Meningkatkan Pedagogik Guru - Iriani, Umi; Hestivik, Chelsi; Fadila, Yosi; Sindo, Pablo; Afriza, Afriza (LPPPI Publishing, 2025)
This study investigates the effectiveness of Learning Management Systems (LMS) in enhancing the pedagogical skills of teachers through online training. In the context of increasing globalization and the need for quality education, the research aims to identify how LMS can bridge the gap in access to professional development, particularly for educators in remote areas. Utilizing a qualitative approach with phenomenological case studies, data were collected through semi-structured interviews and document analysis involving six teachers from UPT SMP Negeri 6 Siak Hulu. The findings reveal that LMS significantly facilitates structured learning by providing easy access to educational resources, tasks, and assessments. Teachers reported positive experiences, highlighting improved organization and interaction in their teaching practices. However, challenges such as unstable internet connectivity and the need for adaptation to new technology were also identified. The study underscores the importance of ongoing support and training for educators to maximize the benefits of LMS. These findings contribute to the broader discourse on integrating technology in education, emphasizing that effective implementation of LMS can enhance teaching quality and student outcomes. Overall, this research advocates for continued investment in technological resources and training to foster an effective learning environment in modern education.